A case study on the use of Virtual Graffiti Portal (VGP) as an agent for e-learning - Izani, M; Paul, A; Razak, AA (2005)
This paper presents a case study on the application of Virtual Graffiti Portal (VGP) as an e-learning agent for open, flexible, and distance education in the Faculty of Creative Multimedia, Multimedia University, Malaysia. VGP is a method of having a virtual discussion in a real time situation. This learning agent is designed mainly to solve some problems in mastering/learning a subjective subject such as visual art. One of the novel contributions is that it allows a virtual discussion in any place at any time. This solves a geographical factor for distance learning and the time constraint issue. Various possibilities can be obtained from this method, such as online chat and real time art discussion, which are made possible by using a virtual drawing board for sketching and drawing. The advantages and disadvantages of this system are discussed together with some proposals for future improvement.